IMPACT FORCE IN SHOULDER DISLOCATION TRAUMA IN TEAM SPORTS - IACOB, Radu Mihai; BUDESCU, Emil; MERTICARU, Eugen (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
This scientific paper presents the biomechanical aspects of the kinetics of the collision of two athletes, with consequences on the traumatism of shoulder dislocation, as well as the ways to reduce the impact force to avoid injury. Using the value of the coefficient of restitution upon collision, based on previous own research, the analytical expression of the impact force is determined, this depending on the instantaneous velocities before and after the collision, on the coefficient of restitution and on the masses of the two athletes. Shoulder dislocation occurs due to the force acting on the humeral head and the joint dislocation from the glenoid cavity of the scapula, this force being the impact force upon collision. Using the game of rugby as an example, the impact forces are calculated for several collisions during a sports competition and then compared with the joint resistance force above which the shoulder joint dislocation can occur. This last force is determined taking into account the mechanical rupture stresses of the articular ligaments, muscles, joint capsule and bone tissue. The paper presents a numerical simulation for determining the pre-collision velocities, for different masses of athletes, so that posterior shoulder dislocation occurs. Also, the paper numerically simulates various situations for the joint resistance force that keeps the scapula-humeral joint in normal operating conditions and then compares this with the impact force from the rugby game.